Antimicrobial activity of aqueous extracts of pomegranate, sumac, sage, anise, hand bull tongue, thyme, cloves, lemon and mint against some food-borne pathogens - Mahmood, Maha A. (The Iraqi Journal of Veterinary Medicine, 2010)
The increasing rate of resistance development for commonly used antibiotics have led to search for newer, more effective, affordable and easily available medicine. Medicinal plants have revived as a consequence of current problems associated with the use of antibiotics. Aqueous extracts of nine plants (pomegranate, sumac, sage, anise, hand bull tongue, thyme, cloves, lemon and mint) were qualitatively and quantitatively examined against twenty microbial isolates, mostly food borne including pathogens. (E.coli, Salmonella typhi and Candida albicans) antimicrobial screening was done by agar diffusion (well diffusion) and minimal inhibitory concentration (MIC) methods. Among the screened plants, cloves were the most inhibitor against isolates of Escherichia coli, Salmonella typhi and Candida albicans followed by the inhibitory effect of sumac against (E.coli, Salmonella typhi and Candida albicans). On the other hand, pomegranate, sage and lemon showed varied inhibitory effect against the tested food borne isolates, whereas the extracts of anise, hand bull tongue, thyme and mint showed no antimicrobial activities against most of the tested isolates. Regarding the inhibition zone and MIC results, the present study certified that Candida albicans was the most sensitive pathogen as compared with the other food borne pathogens tested (Escherichia coli and Salmonella typhi).